2012
DOI: 10.1029/2012wr011958
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent agent for optimal river‐reservoir system management

Abstract: [1] A generalized software package is presented for developing an intelligent agent for stochastic optimization of complex river-reservoir system management and operations. Reinforcement learning is an approach to artificial intelligence for developing a decision-making agent that learns the best operational policies without the need for explicit probabilistic models of hydrologic system behavior. The agent learns these strategies experientially in a Markov decision process through observational interaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
(43 reference statements)
0
13
0
2
Order By: Relevance
“…where the solution is constrained by and must adhere to quality targets [17,42,91]). The mathematical programming techniques applied in this research include linear programming [80,103,178,197], nonlinear programming [17,91,121,150,155,206], dynamic programming [138,174,241], stochastic programming [33,42,70,99,128,139,141,187,207,208,224,225,240], and quadratic programming [86,113].…”
Section: Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…where the solution is constrained by and must adhere to quality targets [17,42,91]). The mathematical programming techniques applied in this research include linear programming [80,103,178,197], nonlinear programming [17,91,121,150,155,206], dynamic programming [138,174,241], stochastic programming [33,42,70,99,128,139,141,187,207,208,224,225,240], and quadratic programming [86,113].…”
Section: Water Qualitymentioning
confidence: 99%
“…Marinoni et al [140] propose a framework for planning major investment decisions and apply this to the case of a water quality enhancement program in a river catchment in Brisbane, Australia. Compromise programming is first used to score the options [42,87,118,121,126,132,139,150,174,176,208,213,224] Storm water [17] Wastewater [1,33,65,80,86,98,106,113,129,139,141,169,187,197,206,219,238] Water allocation [172,230,233] Water trading [224] Water treatment [33,206] Wetlands [39,207,225] for pollution reduction at various sites and the optimal investment problem is then formulated as a multicriteria knapsack problem. In some cases, legislation needs to be considered alongside other management strategies.…”
Section: Water Qualitymentioning
confidence: 99%
“…Rather, the optimization problem is framed as a learning process where an agent (the decision maker) iteratively learn the optimal operating policy by taking actions (decisions) and experimenting the associated costs/rewards from the environment (the system). Single objective Reinforcement Learning has been extensively studied and experimented in many engineering applications, with several studies reported also in the water resources literature [ Lee and Labadie , ; Castelletti et al ., ; Rieker and Labadie , ]. On the other hand, multiobjective Reinforcement Learning (MORL) is still a relatively unexplored research area and, to the authors' knowledge, there have been no applications of MORL to water resources management.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated the superiority of Q-learning over the other two approaches. Other examples of Q-learning applied for water resources systems can be found in Bhattacharya et al (2003), Mariano-Romero et al (2007), Mahootchi et al (2007), Mahootchi et al (2010), and Rieker and Labadie (2012). Castelletti et al (2010) applied the fitted Q-iteration combined with tree-based regression to form a suitable function approximator in daily operation of a single reservoir system in Italy.…”
mentioning
confidence: 99%